Skuteczna nauka języka obcego na zajęciach online - Potempska, Justyna (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
The aim of the article is to discuss methodological and didactic issues related to the foreign language classes conducted remotely and to show the potential that lies in the use of Internet tools in online foreign language teaching. The main question that guides the considerations here relates to the effectiveness of learning through online platforms and applications. The author analyses the specifics of online classes and points out what to pay special attention to while conducting them.